(untitled) (Research, Society and Development, 2022)
It deals with the research on Executive feasibility of precast ramps, from the perspective of civil engineering. Prefabricated pedestrian ramps are slip-resistant and low maintenance, while prefabricated loading ramps are pre-engineered and customizable by length, width and height. objective to discuss the way of building precast ramps approaching the structure made in engineering. This study, because it is a bibliographical research, brought scholars in the area that show how important analysis of the feasibility of the execution of precast ramps is and to conclude that cast-in-place concrete is more financially viable in the short term, the pre-cast molding that needs skilled labor and heavy machinery, which would be a great disadvantage in the long run, making the work in molded-in-place economically more advantageous.